Question and Answers Forum

All Questions      Topic List

Differential Equation Questions

Previous in All Question      Next in All Question      

Previous in Differential Equation      Next in Differential Equation      

Question Number 99286 by bobhans last updated on 20/Jun/20

Commented by bemath last updated on 20/Jun/20

Bernoulli equation

Bernoulliequation

Commented by bemath last updated on 20/Jun/20

y′ + (1/x)y = ((cos x)/y^2 )  y′+ (1/x)y = (cos x ).y^(−2)   let u = y^(1−(−2))  = y^3    (du/dx) = 3y^2  (dy/dx) , (dy/dx) =(1/3) y^(−2)  (du/dx)  ⇔(1/3)y^(−2)  (du/dx) + (1/x)y = (cos x).y^(−2)   (du/dx) + (3/x)u = cos x   IF v (x) = e^(∫ (3/x) dx) = e^(3 ln(x))  = x^3   ⇔u(x) = ((∫ x^3 cos x dx +C)/x^3 )  x^3 y^3  = x^3 sin x+3x^2 cos x−6xsin x−6cos x +C  y^3  = sin x + ((3cos x)/x)−((6sin x)/x^2 )−((6cos x)/x^3 )+Cx^(−3)

y+1xy=cosxy2y+1xy=(cosx).y2letu=y1(2)=y3dudx=3y2dydx,dydx=13y2dudx13y2dudx+1xy=(cosx).y2dudx+3xu=cosxIFv(x)=e3xdx=e3ln(x)=x3u(x)=x3cosxdx+Cx3x3y3=x3sinx+3x2cosx6xsinx6cosx+Cy3=sinx+3cosxx6sinxx26cosxx3+Cx3

Commented by bobhans last updated on 20/Jun/20

great

great

Terms of Service

Privacy Policy

Contact: info@tinkutara.com